Peran Orang Tua Dalam Mendidik : Studi Kasus Kenakalan Remaja - Natanael Situmorang, Yohanes; Hengka Nove, Albertus; Br. Manik, Renonsi; Wani Giawa, Jui Samarta; Hutauruk, Filia; Robin Pakpahan, Daud (Universitas Palangka Raya, 2024)
The purpose of this study is to describe the importance of the role of parents in dealing with juvenile delinquency. The findings show that there are several attitudes and behaviors shown by parents in dealing with juvenile delinquency such as (1) good communication and constructive and educational advice; (2) providing positive role models for children; (3) providing discipline to children, and (4) giving praise to children when doing good things. Based on these findings, it can be concluded that the role of parents in dealing with juvenile delinquency plays an important role in adolescent growth and development. The limitation in this study is that researchers only see the causes of juvenile delinquency from the role of parents so that further research can reveal a wider range of causes of juvenile delinquency such as the role of peers, the role of social media and the impact of broken homes.